2020
DOI: 10.1021/acssuschemeng.0c05049
|View full text |Cite
|
Sign up to set email alerts
|

Polarclean/Water as a Safe and Recoverable Medium for Selective C2-Arylation of Indoles Catalyzed by Pd/C

Abstract: Herein, we report the use of nontoxic, water-miscible Polarclean as a safe dipolar aprotic solvent for the metal-catalyzed direct C2–H arylation of indoles using Pd/C as a catalyst. The developed method allows reaching excellent yields and regioselectivities, and it tolerates various substituents on both indole and diaryliodonium salt scaffolds. Polarclean is fully recoverable and reusable; it shows a very low leaching of the metal catalyst, allowing its complete recovery and reuse for at least six representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 88 publications
(159 reference statements)
0
12
0
Order By: Relevance
“…However, its high viscosity compared with other common solvents used in SPPS (Table 1) could impair its diffusion through the polymeric matrix and therefore preclude its use in this strategy. Despite this adverse property and given the good performance of PolarClean in other chemical industrial applications (20)(21)(22)(23), here we examined its compatibility in fluorenylmethloxycarbonyl (Fmoc)/tert-butyl (tBu) SPPS using PS resin, which is the most common and affordable solid support used. To be considered suitable for use in SPPS, solvents must show the good capacity to solubilize reagents and swell resin, and they must also be compatible with the conditions used for peptide coupling and protecting group removal.…”
Section: Resultsmentioning
confidence: 99%
“…However, its high viscosity compared with other common solvents used in SPPS (Table 1) could impair its diffusion through the polymeric matrix and therefore preclude its use in this strategy. Despite this adverse property and given the good performance of PolarClean in other chemical industrial applications (20)(21)(22)(23), here we examined its compatibility in fluorenylmethloxycarbonyl (Fmoc)/tert-butyl (tBu) SPPS using PS resin, which is the most common and affordable solid support used. To be considered suitable for use in SPPS, solvents must show the good capacity to solubilize reagents and swell resin, and they must also be compatible with the conditions used for peptide coupling and protecting group removal.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Pd/C was successfully applied by Vaccaro et al in the C2 direct arylation of free NH indoles with diaryliodonium salts as arylating agents: reactions worked well for 5-substituted indoles (30-93% yields), but failed with 3-methyl indole. 48 Although diaryliodonium salts are typically characterized by a low atom economy, such protocol exhibited great attention to sustainability, corroborated by the use of PolarClean/water as a safe and recoverable reaction medium, and by the good recyclability of Pd/C (up to six runs) without lowering the yield and low Pd leaching (≤1.0 ppm).…”
Section: Recoverable Palladium-based Catalysts For Direct C-h Bond Ar...mentioning
confidence: 99%
“…In 2020, an interesting study was reported by Vaccaro et al: they described a C2 regioselective direct C-H bond arylation of indoles with diaryliodonium salts, using a Rhodiasolv® PolarClean/H 2 O mixture 1 : 4 (v/v) as a safe and recoverable reaction medium. 48 In fact, PolarClean is a promising solvent that can reduce the carbon footprint; it is produced on ton scale by Solvay in a circular economy approach, it is not toxic and is highly biodegradable. Although iodonium salts are arylating agents typically characterized by a low atom economy, this protocol exhibited a great attention to sustainability, strengthened by the use of Pd/C as a recyclable supported catalyst (see section 2.1.2).…”
Section: Direct C-h Bond Arylation Of (Hetero)arenes In Watermentioning
confidence: 99%
“…The method showed excellent yields and regioselectivities, and it tolerated various substituents on both indole and diaryliodinium tetrafluoroborate (Scheme 81). PC used in the reaction is highly recoverable and reusable providing waste minimized synthesis by very low leaching of used catalyst [87] …”
Section: Transformations Involving Hypervalent Iodine Reagents and 2 ...mentioning
confidence: 99%